Implementasi Model Pembelajaran Project Based Learning pada Mata Pelajaran Bahasa Indonesia - Fakhru Ahsani, Eva Luthfi; Taqiyah, Barirotut (the Study Program of Education for Islamic Elementary School Teachers (Undergraduate), 2024)
This research was carried out because of students' interest in practical learning models which were aimed at finding out the application of the Project based Learning model as well as the inhibiting and supporting factors encountered in the process of implementing it in Indonesian language learning in class IV MI Tarbiyatul Islamiyah Srikaton. Researchers used field research with a qualitative approach. The data obtained was collected through interviews with related parties, namely educators and class IV students, and observation. Researchers use data reduction, presentation and also draw data conclusions in the analysis process. The results obtained in the form of application of learning include planning and implementation processes which include the steps of determining basic questions, preparing plans, preparing schedules, monitoring, testing results and evaluating experience. Supporting factors for implementing the Project Based Learning learning model are professional teachers, enthusiastic students, adequate educational facilities. The inhibiting factors are the presence of some students who are less responsive and the school environment is too busy.